Expression of Superoxide Dismutase Enzyme in Stress Conditions - Politeo, O.; Carev, I.; Ferhatović Hamzić, L. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Reactive oxygen species (ROS) play a key role in the initiation and progression of many human diseases. Superoxide anion radical (O2•-), arising continuously in the cells, is one of the most important and biologically relevant ROS radicals in living organisms. Superoxide dismutase (SOD) is an enzyme important in the process of cellular responses to stress conditions. Using the WST spectrophotometric method, the effect of insulin-dependent diabetes mellitus (IDDM) on SOD expression in tissues of aging rats was investigated. A rat model for IDDM was established by streptozotocin application. Rats were randomly divided into 4 groups: DM-2W (streptozotocin-treated, sacrificed after 2 weeks), control-2W, DM-1Y (streptozotocin-treated, sacrificed after 1 year), and control-1Y. Results showed overexpression of SOD enzyme in both DM-2W and DM-1Y groups compared with control groups. The stronger overexpression in DM-2W could be explained by fading of the organism's defence system over time.